2019
DOI: 10.1002/hed.25633
|View full text |Cite
|
Sign up to set email alerts
|

Depth of invasion alone as an indication for postoperative radiotherapy in small oral squamous cell carcinomas: An International Collaborative Study

Abstract: Background We aimed to investigate whether depth of invasion (DOI) should be an independent indication for postoperative radiotherapy (PORT) in small oral squamous cell carcinomas (SCC). Methods Retrospective analysis of DOI (<5, 5 to <10, ≥10 mm) and disease‐specific survival (DSS) in a multi‐institutional international cohort of 1409 patients with oral SCC ≤4 cm in size treated between 1990‐2011. Results In patients without other adverse factors (nodal metastases; close [<5 mm] or involved margins), there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 30 publications
(93 reference statements)
1
33
0
Order By: Relevance
“…, the tumor DOI is not yet a criterion for radiation therapy for patients with cN0 (Ganly et al, ) . Accordingly, a recent multicenter study showed that DOI alone should not be indicative for postoperative radiotherapy in early‐stage OSCC in the absence of other adverse features (Ebrahimi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…, the tumor DOI is not yet a criterion for radiation therapy for patients with cN0 (Ganly et al, ) . Accordingly, a recent multicenter study showed that DOI alone should not be indicative for postoperative radiotherapy in early‐stage OSCC in the absence of other adverse features (Ebrahimi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“… 35 Moreover, in the absence of other adverse pathological features, DOI should not be an independent indication for postoperative radiotherapy in small OSCC. 36 With regard to the implementation of END, Akira Baba et al reported that oral tongue cancer undetectable on magnetic resonance imaging (MRI) indicated a high possibility of pathological DOI smaller than 4 mm, which can be used as a criterion to avoid unnecessary END in node-negative patients. 37 Nevertheless, MRI evidence of invasion to the styloglossus and hyoglossus muscles corresponds to a DOI greater than 4 mm, which can be a criterion for the advisability of END.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the above findings, HDFs had little effect on the biological characteristics of OSCC. Cutaneous squamous cell carcinoma (CSCC) has a better prognosis than OSCC, and CSCC rarely invades deep into the skin tissue [ 15 , 16 , 17 ], whereas OSCC has significant invasion ability [ 18 ]. Although both CSCC and OSCC develop from the epithelium in a similar manner, their infiltration ability and prognosis are quite different.…”
Section: Discussionmentioning
confidence: 99%